2004
DOI: 10.1007/s00595-003-2677-1
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Antibiotics and Saccharomyces boulardii on Bacterial Translocation in Burn Injury

Abstract: These results suggest that the incidence of BT in burn injury is enhanced by using an antibiotic, and that S. boulardii decreases the incidence of antibiotic-induced BT. Thus, we conclude that S. boulardii can effectively protect the intestinal ecologic equilibrium and prevent BT in burn injury victims.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 41 publications
0
13
0
Order By: Relevance
“…As described by Berg (1995), translocation to liver could occur via intracellular passage (lymphatic route, via lymph nodes) or extracellular passage (vascular route, due to physical damage to the intestinal epithelium). Reduced levels of translocation have been also observed in various animal models (burn injury, liver injury, experimental immunosuppression, abdominal infection) using probiotic products based on bacteria (Chiva et al, 2002;Gun et al, 2005) and yeast (Peret et al, 1998;Herek et al, 2004). It seems that all the components of the host immune systemincluding mucosal, cell-mediated and humoral immunities -are involved in controlling bacterial translocation.…”
Section: Discussionmentioning
confidence: 97%
“…As described by Berg (1995), translocation to liver could occur via intracellular passage (lymphatic route, via lymph nodes) or extracellular passage (vascular route, due to physical damage to the intestinal epithelium). Reduced levels of translocation have been also observed in various animal models (burn injury, liver injury, experimental immunosuppression, abdominal infection) using probiotic products based on bacteria (Chiva et al, 2002;Gun et al, 2005) and yeast (Peret et al, 1998;Herek et al, 2004). It seems that all the components of the host immune systemincluding mucosal, cell-mediated and humoral immunities -are involved in controlling bacterial translocation.…”
Section: Discussionmentioning
confidence: 97%
“…BT is caused and enhanced by hemorrhagic shock, burn injury, intestinal obstruction, total parenteral nutrition, antibiotic therapy, malnutrition and trauma [10, 11, 12, 13, 14, 15]. Physiopathological events causing BT have not yet been fully elucidated, but three major mechanisms have been proposed to explain this process: (1) bacterial overgrowth; (2) impairment in host immune defenses, and (3) increased permeability of the intestinal mucosal barrier [5, 6, 16].…”
Section: Discussionmentioning
confidence: 99%
“…21 S. boulardii has been used in the treatment of intestinal disorders in recent studies. [22][23][24][25] Berg et al 19 reported that bacterial translocation is caused by oral antibiotics due to the disruption of the gastrointestinal ecological equilibrium, leading to intestinal overgrowth. However, they also reported that S. boulardii is widely used as a probiotic which decreases the incidence of Candida albicans translocation to the MLNs, liver, and kidneys.…”
Section: Table 2 the Average Of Serum Bilirubin Alt Ast And Alp Valmentioning
confidence: 99%